1997
DOI: 10.4067/s0717-71781997002500013
|View full text |Cite
|
Sign up to set email alerts
|

Toxicidad del cobre en larvas nauplii del camarón comercial Artemesia longinaris Bate (Crustacea, Decapoda, Penaeidae)

Abstract: RESUMEN. Se evaluó la toxicidad del cobre, empleando sulfato de cobre en larvas nauplii sin alimentar del camarón comercial Artemesia longinaris mediante bioensayos de 72 horas de duración, con el objeto de determinar la dosis efectiva media o concentración letal (LC50) y grado de desarrollo (estadio larval). Se prepararon concentraciones de cobre equivalentes a 1000, 500, 250 y 125 partes por billón (ppb) en agua de mar (salinidad de 34 %). Un total de 90 larvas nauplii por tratamiento (tres réplicas de 30 la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
1
9
0
8
Order By: Relevance
“…Copper toxicity for L. santolla was in the same order of magnitude as in other crustacean larvae ( Munshi et al, 1996;Ramachandran et al, 1997;Scelzo, 1997;López Greco et al, 2001;Ferrer et al, 2003). Copper was one order of magnitude more toxic than other metals assayed on the same species and larval stage, resulting in the following relative scale of acute lethal toxicity: Cu>Pb>Cd>Zn (Amin et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…Copper toxicity for L. santolla was in the same order of magnitude as in other crustacean larvae ( Munshi et al, 1996;Ramachandran et al, 1997;Scelzo, 1997;López Greco et al, 2001;Ferrer et al, 2003). Copper was one order of magnitude more toxic than other metals assayed on the same species and larval stage, resulting in the following relative scale of acute lethal toxicity: Cu>Pb>Cd>Zn (Amin et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…Water in experimental tanks was filtered (5 μm) and passed through a UV lamp. To prevent diseases, parasites or bad water quality, water was treated with the following chemicals: EDTA (0.5 mg L -1 ; Scelzo, 1998), iodine (dissolved at 1.75%), calcium hydroxide (20 mg L -1 ; Mallo & Fenucci, 2004), copper sulfate (125 mg L -1 ; Scelzo, 1997), formaldehyde (1×10 -5 ppt; Hernández-Valencia, 2010) and sulfamethoxazoletrimethoprim (4×10 -2 ppt; 23,750 mg +1,250 mg; Laganà et al, 2011). A 5 hp blower (Sweetwater®, Apopka, FL, USA) and diffusers were used to maintain continuous aeration.…”
Section: General Proceduresmentioning
confidence: 99%
“…First, biologically active copper has remained chronically high in Caleta Palito and surroundings due to the mine tailing discharge (Andrade et al 2006) and to the re-suspension of old coastal sediment. Second, although copper is an essential micronutrient for normal growth and development (Lesser 2006), and in decapods it is a fundamental component of hemocyanin, excessive amounts of this metal are lethal to crustaceans (Scelzo 1997). Different authors have reported a gradual loss of the osmoregulatory function and diminished gas exchange in decapod crustaceans when exposed to increasing concentrations of copper (Spicer & Weber 1992).…”
Section: Discussionmentioning
confidence: 99%